2013
DOI: 10.1080/00063657.2012.758228
|View full text |Cite
|
Sign up to set email alerts
|

Avian foraging behaviour in relation to provision of ecosystem services in a highland East African agroecosystem

Abstract: (2013) Avian foraging behaviour in relation to provision of ecosystem services in a highland East African agroecosystem, Bird Study, 60:2, 156-168,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…One limiting factor in agriculture, particularly in the developing world, is the availability of expensive inputs, such as fertilizers and pesticides (Ndang'ang'a et al 2013). By encouraging the provisioning of ecosystem services, including pest control, farmers could decrease their reliance on costly chemical inputs.…”
Section: List Of Tablesmentioning
confidence: 99%
“…One limiting factor in agriculture, particularly in the developing world, is the availability of expensive inputs, such as fertilizers and pesticides (Ndang'ang'a et al 2013). By encouraging the provisioning of ecosystem services, including pest control, farmers could decrease their reliance on costly chemical inputs.…”
Section: List Of Tablesmentioning
confidence: 99%
“…In case of any sticky mud, the sample was first diluted in a bucket of water and then sieved [31]. Dry soil samples were sorted by hand [32,33]. This method was clearly biased to soil macroinvertebrates.…”
Section: Invertebrate Abundancementioning
confidence: 99%
“…Yet, the supposition that coffee grown without shade (sun coffee) provides higher quantity yields than shade coffee is unproven; in fact, recent research has reported that up to 50% shade cover on farms has a positive effect on coffee yields both in quantity and quality due to temperature regulation, shade tree nitrogen fixation, reduction of coffee related pests, and decreased spread of coffee‐effecting diseases (Atallah et al., 2016; Avelino et al., 2015; Cerda et al., 2017; Coffee Research Institute, 2019; Jha et al., 2014; Jonsson et al., 2015; Maas et al., 2013, 2016; Meylan et al., 2017; Soto‐Pinto et al., 2000). Shade negatively impacts coffee pests by lowering temperatures below pests’ thermal optima and also contributes to pest control through increased predation by birds (Johnson et al., 2010; Kariuki Ndang'ang'a et al., 2013; Karp et al., 2013; Kellermann et al., 2008; Maas et al., 2016; Mäntylä et al., 2011; Perfecto et al., 1996, 2014; Railsback & Johnson, 2014). Studies in the Neotropics have shown that increased predation may be a function of overall bird abundance or diversity (Van Bael et al., 2008; Martínez‐Salinas et al., 2016; Sekercioglu, 2012).…”
Section: Introductionmentioning
confidence: 99%